Fructidor - Fremaux, Louis; State Theatre (Sydney, N.S.W.) (1900)
Part of the State Theatre collection of cinema scores and parts, mainly used for silent movies, but including musical materials associated with talking pictures ca. 1900-1950, used by the State Theatre and various film distribution companies throughout Australia. Some items include performance annotations.
The music is in an annotated folder that shows lending date, place or name of cinema.
Keywords: Silent film music; Instrumental music -- Scores and parts; Dramatic music